Successful Kidney Transplantation in a Recipient Coinfected with Hepatitis C Genotype 2 and HIV from a Donor Infected with Hepatitis C Genotype 1 in the Direct-Acting Antiviral Era - Dimitrios Farmakiotis; Zoe Weiss; Amy L. Brotherton; Paul Morrissey; Reginald Gohh; Kendra Vieira; Lynn E. Taylor; Joseph M. Garland (Case Reports in Hepatology)
Despite significant advances in transplantation of HIV-infected individuals, little is known about HIV coinfected patients with hepatitis C virus (HCV) genotypes other than genotype 1, especially when receiving HCV-infected organs with a different genotype. We describe the first case of kidney transplantation in a man coinfected with hepatitis C and HIV in our state. To our knowledge, this is also the first report of an HIV/HCV/HBV tri-infected patient with non-1 (2a) HCV genotype who received an HCV-infected kidney graft with the discordant genotype (1a), to which he converted after transplant. Our case study highlights the following: (1) transplant centers need to monitor wait times for an HCV-infected organ and regularly assess the risk of delaying HCV antiviral treatment for HCV-infected transplant candidates in anticipation of the transplant from an HCV-infected donor; (2) closer monitoring of tacrolimus levels during the early phases of anti-HCV protease inhibitor introduction and discontinuation may be indicated; (3) donor genotype transmission can occur; (4) HIV/HCV coinfected transplant candidates require a holistic approach with emphasis on the cardiovascular risk profile and low threshold for cardiac catheterization as part of their pretransplant evaluation.